The Student's Perception of The Use of The Google Form Application for Assessment at Senior High School - Visser, Lodovikus Eussabeus; Mustofa, Mutmainnah; Elfiyanto, Soni (Universitas Nahdlatul Ulama Blitar, 2023)
Google Forms is an educational application that teachers use in teaching activities to assess students. Teachers usually create questions, quizzes, and assessments through Google Forms. This research investigated the student's perception of the Google Form application as an instrument for assessment that teachers use. The researcher used a quantitative descriptive method through an online Malang senior high school students’ questionnaire. Twenty-nine students have used Google Forms in English learning for assessment, and to get more information about their perceptions in experiences using it, the researcher needs to give 16 questions in online questionnaires. The researchers found more than a few issues that stimulus the students' online learning process in assessment: In terms of utility, convenience of use, ease of learning, and satisfaction, 62.0% of participants believed that Google Forms is practical. 51.1% of them agree that the application is simple to use. The next component also agrees that 57.1% of the students went through easiness to learn how to utilize the software. The last is about the level of satisfaction; 61.8% of the students experience satisfaction. The results showed that oogle Forms can be very helpful in boosting students' abilities, skills, discipline, and impartial learning through instructional resources.